Analisis Bentuk, Pola Pelaksanaan dan Peran ‘Basiru’ dalam Pembangunan Pedesaan di Desa Selante Kabupaten Sumbawa - Sumarlin Sumarlin; Anton Anton; Ismiati Ismiati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
One widely applied strategy for accelerating rural development is the "mutual help tradition." People in Sumbawa Regency call it 'Basiru.' Today, only a few villages in Sumbawa still claim and preserve 'Basiru' as a valuable tradition, one of which is Selante Village. This study was conducted from April until September 2022 and aimed to analyze and describe the forms, implementation patterns, and roles of 'Basiru' in the rural development of Selante Village. Data was collected through participated observation, in-depth interviews, and Focus Group Discussion (FGD). The number of the informant was ten; they were the village government, community leaders, and the residents who briefly recognized and understood Selante village's cultures. The data is analyzed by organizing it, describing it, synthesizing it, compiling it into patterns, choosing which ones are important, and making conclusions. The finding shows there are three forms of 'Basiru' implemented in Selante Village, namely; (1) 'Basiru' Services, (2) 'Basiru' Money, and (3) 'Basiru' Goods. Those forms of 'Basiru' are carried out in agricultural, infrastructure construction, social activities, livestock, and educational activities. 'Basiru' is used as a rural development instrument in infrastructure construction, the arrangement of the community's economic and social character and culture in Selante Village.